Effectiveness of the use of various digital applications to promote public health in Indonesia: A study of the impact of technology on public health - Budi Sulistiyo Nugroho Nugroho; Maulana Filani Rizal; B.M.A.S. Anaconda Bangkara; Leila Mona Ganiem; Reza Yuridian Purwoko (Science Midwifery, 2022)
This study was conducted to gain an in-depth understanding of what and how effective the use of digital applications to promote public health is due to the increasingly powerful impact of technology, including public health. This elephant utilizes the data we search electronically on compounds of health publications and technologies released between 2010 and 2022. We examine them under a biological approach that involves a series of techniques such as coding the data, evaluating the data thoroughly, and approaching conclusions so that we will get answers. Finally, digital applications to promote public health, especially in Indonesia, are a non-negotiable necessity, considering the effectiveness and innovation provided by technology that can complete health tasks that have been carried out manually. These findings will be helpful for further studies.